(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the rate of anemia in pregnant women coming to make birth registration at Ha Dong General Hospital in 2024 and some related factors. Subject and method: Cross-sectional study on 284 pregnant women who came for prenatal check-ups and completed antenatal records from August 1, 2024 to September 30, 2024. Results: In our study, the rate of anemic pregnant women was 25.35%, of which moderate anemia accounted for 1.4% and mild anemia accounted for 23.95%. The mean age of the anemic group was 28.56 ± 5.6, lower than that of the non-anemic group. Related factors include maternal weight gain less than 12 kg, inadequate iron supplementation, birth spacing, and first-time pregnancy, which are factors that increase the risk of anemia during pregnancy. Conclusion: The rate of pregnant women coming to the Ha Dong General Hospital for examination and making birth records is high, related to inadequate iron supplementation, maternal weight gain below 12 kg, and birth spacing. Therefore, it is necessary to strengthen interventions and nutrition and health education for pregnant women to reduce anemia in this community.